2011
DOI: 10.1111/j.1365-2966.2011.18448.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the intrinsic AGN infrared spectral energy distribution and measuring its contribution to the infrared output of composite galaxies★

Abstract: We use infrared spectroscopy and photometry to empirically define the intrinsic mid‐ to far‐infrared spectral energy distribution (i.e. 6–100 μm SED) of thermal emission produced by typical (i.e. 2–10 keV luminosity, L2‐10 keV∼ 1042–1044 erg s−1) active galactic nuclei (hereafter AGNs). The average infrared SED of typical AGNs is best described as a broken power law at ≲40 μ m that falls steeply at ≳40 μm (i.e. at far‐infrared wavelengths). Despite this fall‐off at long wavelengths, at least three of the 11 AG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
694
7
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(761 citation statements)
references
References 75 publications
(270 reference statements)
58
694
7
2
Order By: Relevance
“…---- , significantly lower than the value expected from pure AGNs (e.g., Mullaney et al 2011). Considering the observed 2-10 keV luminosity, the ratio is L L log 4.14 Using the relationship of Mullaney et al (2011) it is possible to convert the 2-10 keV luminosity into the expected IR ( ( ) ) = -we find that the IR luminosity of the AGN is between 0.1% and 0.6% of the total IR luminosity.…”
Section: Agn Contribution To the Ir Luminositymentioning
confidence: 93%
“…---- , significantly lower than the value expected from pure AGNs (e.g., Mullaney et al 2011). Considering the observed 2-10 keV luminosity, the ratio is L L log 4.14 Using the relationship of Mullaney et al (2011) it is possible to convert the 2-10 keV luminosity into the expected IR ( ( ) ) = -we find that the IR luminosity of the AGN is between 0.1% and 0.6% of the total IR luminosity.…”
Section: Agn Contribution To the Ir Luminositymentioning
confidence: 93%
“…The Herschel Space Observatory (Pilbratt et al 2010), with its high FIR sensitivity and broad wavelength coverage, offers a powerful way of measuring the approximate SFR with minimal AGN contamination (e.g. Netzer et al 2007;Hatziminaoglou et al 2010;Mullaney et al 2011;Bonfield et al 2011;Hardcastle et al 2013;Virdee et al 2013). However, a drawback of previous works is that they are fundamentally limited by the strong correlation between redshift and luminosity, i.e., only the most powerful sources are observed at high redshifts and, due to the much smaller volume probed, only the less luminous, more abundant populations are found at lower redshifts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mullaney et al (2011) subtracted the host-galaxy contribution from the observed 6-100 μm IR SEDs of a sample of local galaxies hosting an AGN to derive the IR emission intrinsic to the AGN. When we compare the observed SED of SAGE1CJ053634 with the intrinsic SEDs presented in Mullaney et al (2010) we find a very good agreement.…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated this possibility by comparing the observed PAH emission with the starburst galaxy templates of Mullaney et al (2011). These templates were derived by mean averaging similar SEDs from groups of galaxies that cover the full range of IR colours of starburst and Luminous InfraRed galaxies in the local Universe.…”
Section: The Origin Of the Pah Bandsmentioning
confidence: 99%